2019
DOI: 10.1177/1947603519855759
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MEG3 Inhibits the Degradation of the Extracellular Matrix of Chondrocytes in Osteoarthritis via Targeting miR-93/TGFBR2 Axis

Abstract: Background As a degenerative joint disease, osteoarthritis (OA) is characterized by articular cartilage degradation. Long noncoding RNAs (lncRNAs) act critical roles in the regulation of OA development, including affecting the proliferation, apoptosis, extracellular matrix (ECM) degradation, and inflammatory response of chondrocytes. The current study’s aim was to investigate the regulatory function and the underlying molecular mechanism of lncRNA MEG3 in ECM degradation of chondrocytes in OA. Methods In the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 45 publications
(51 reference statements)
2
35
0
Order By: Relevance
“…We showed a particular enrichment of lincRNAs in the differential expression analysis (17.8% to 34.6% figure 2), showing that lincRNAs indeed play an important role in the OA pathophysiology as seen in previous studies [8,16,28]. Nonetheless, in comparison to the fraction of FDR significant DE lncRNAs reported by Pearson et al [8], this fraction is still Of the 191 FDR significant DE lncRNAs between lesioned and preserved OA cartilage (figure 3), multiple lncRNAs were previously found, including MEG3, LINC01614, and PART1 [16,24]. Nonetheless, there were also examples of lncRNAs previously associated to OA, which were expressed but not FDR significantly different, such as MALAT1, HOTAIR, GAS5, and TUG1 [25][26][27].…”
Section: Discussionsupporting
confidence: 53%
“…We showed a particular enrichment of lincRNAs in the differential expression analysis (17.8% to 34.6% figure 2), showing that lincRNAs indeed play an important role in the OA pathophysiology as seen in previous studies [8,16,28]. Nonetheless, in comparison to the fraction of FDR significant DE lncRNAs reported by Pearson et al [8], this fraction is still Of the 191 FDR significant DE lncRNAs between lesioned and preserved OA cartilage (figure 3), multiple lncRNAs were previously found, including MEG3, LINC01614, and PART1 [16,24]. Nonetheless, there were also examples of lncRNAs previously associated to OA, which were expressed but not FDR significantly different, such as MALAT1, HOTAIR, GAS5, and TUG1 [25][26][27].…”
Section: Discussionsupporting
confidence: 53%
“…The 191 lncRNAs identified in this study included several previously found to be associated with OA, such as MEG3 (fold change 0.6, FDR 8.8 × 10 −3 ), PART1 (fold change 1.8, FDR 1.7 × 10 −4 ), and LINC01614 (fold change 2.6, FDR 9.5 × 10 −3 ) (16,26), as well as novel OA‐associated lncRNAs, including P3H2‐AS1 (fold change 2.7, FDR 4.1 × 10 −4 ) and AC090877.2 (fold change 0.3, FDR 6.2 × 10 −5 ). Notably, previously identified lncRNAs such as MALAT1 (fold change 1.3, FDR 0.4) (27), TUG1 (fold change 1.1, FDR 0.7) (28), HOTAIR (fold change 0.8, FDR 0.5), and GAS5 (fold change 1.1, FDR 0.8) (29) were not found to be significantly differentially expressed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…As a kind of noncoding RNA, lncRNA can function as ceRNA and restrain miRNA by lncRNA-miRNA sponge in cancer, cardiovascular disease, and so on [25,26]. Several functional lncRNAs have been demonstrated to influence osteoblast differentiation and OA pathogenesis through lncRNA-miRNA-mRNA ceRNA mechanism [27][28][29][30]. Some lncRNAs can affect the degradation of the extracellular matrix of chondrocytes by functioning as ceRNAs of specific miRNAs and thus participate in the development and progression of OA, such as lncRNAs of HOTTIP, MEG3, and XIST [28,29,31].…”
Section: Lncrna Ighcγ1 Promoted Inflammation Bymentioning
confidence: 99%
“…Several functional lncRNAs have been demonstrated to influence osteoblast differentiation and OA pathogenesis through lncRNA-miRNA-mRNA ceRNA mechanism [27][28][29][30]. Some lncRNAs can affect the degradation of the extracellular matrix of chondrocytes by functioning as ceRNAs of specific miRNAs and thus participate in the development and progression of OA, such as lncRNAs of HOTTIP, MEG3, and XIST [28,29,31]. Some lncRNAs have been well documented to regulate the differentiation of osteoblasts via the lncRNA-miRNA ceRNA network [27].…”
Section: Lncrna Ighcγ1 Promoted Inflammation Bymentioning
confidence: 99%